The Influence of Cash Ratio, Net Profit Margin, and Company Size on Dividend Policy - Dea Anggraini; Utami, Ranti; Afriyadi; Novica Indriaty; Tommy Munaf (Basic and Applied Accounting Research Journal, 2024)
The purpose of this study was to determine the effect of cash ratio, net profit margin and company size on dividend policy in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2018-2022. The research method used in this research is quantitative. The population in this study were 58 main board consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used in this study was purposive sampling. So that the sample obtained was 21 consumer non-cyclicals companies listed on the IDX for the 2018-2022 period. The results showed that partially cash ratio and net profit margin had no effect on dividend policy. Meanwhile, company size partially has a significant effect on dividend policy. It can be concluded that cash ratio, net profit margin and company size have an effect on dividend policy. And the Adjusted R-Squared value is 0.736174, which means that the dividend policy is influenced by the Cash Ratio, Net Profit Margin and Company Size by 73.62% and 26.38% is influenced by other variables not examined in this study.